Accurate, sensitive and rapid determination of perchlorate in tea by hydrophilic interaction chromatography-tandem mass spectrometry. Issue 28 (1st July 2020) - Wang, Chen; Chen, Hongping; Zhu, Li; Liu, Xin; Lu, Chengyin
Abstract : An accurate, sensitive and rapid method for determination of perchlorate in tea by hydrophilic interaction chromatography-tandem mass spectrometry. Abstract : Perchlorate is an environmental contaminant interrupting thyroid hormone production, and perchlorate in tea has raised wide concern recently. In this study, an accurate method was developed for the determination of perchlorate in tea using hydrophilic interaction chromatography-tandem mass spectrometry and a simplified QuEChERS procedure. The method utilized a zwitterion HILIC column for separation, and the optimal gradient eluents consisted of acetonitrile and aqueous solution with 0.1% formic acid and 20 mmol L −1 ammonium formate. Calibration curves were fitted by the quadratic model with 1/ x weight instead of the linear model. As perchlorate was only partially extractable when using acetonitrile or methanol as the extraction solvent, acetonitrile/water (1 : 1, v/v) was chosen to extract perchlorate from tea samples. Graphitized carbon black was used as the dispersive solid phase extraction sorbent to clean up tea extracts. The method exhibited satisfactory accuracy with recoveries of 81.4–100.9% and relative standard deviations of 1.3–14.5% for green and black teas. The limit of quantitation was 0.005 mg kg −1, while the limits of detection were 0.0011 mg kg −1 for green tea and 0.0013 mg kg −1 for black tea, indicating an excellent sensitivity of this method. A 100% positive rate of perchlorate was found in 100 real tea samples, and the concentrations ranged from 0.0030 mg kg −1 to 0.78 mg kg −1 . This accurate, sensitive and rapid method would be suitable for monitoring, risk assessment and source identification of perchlorate in tea.